Compact Corner Truncated Fractal Slot Antenna for Cognitive Radio Sensor Network. Issue 1 (2nd January 2023) - Goswami, P. K.; Goswami, G.
Abstract : The cognitive radio (CR) opens new paradigms of opportunistic utilization of unused frequency spectrum through spectrum sharing. Dynamic spectrum access (DSA) provides an effective solution to channel congestion with the help of software-defined radio in cognitive radio networks (CRN). Software defined radio (SDR) offers manipulative wide spectrum sensing and reconfigurable transmission properties between licensed primary user (PU) and unlicensed secondary user (SU). The opportunistic spectrum sharing elicits the need for hardware compatibility from a common radiating antenna for extra-large band spectrum scanning. This paper proposes a novel compact antenna for wide spectrum sensing to utilize vacant channel opportunity in wireless cognitive radio sensor network (WCRSN). The antenna design comprises the combinational effects of fractal slots and electromagnetic bandgap structure on compact FR4 substrate 12 × 18 × 1.6 mm 2 . The circular polarization improves the feasibility of antenna for orientation-free scanning of spectrum through corner truncation. The novel antenna design exhibits large measured impedance bandwidth from 0.79 to 12.0 GHz compatible with Zigbee, Bluetooth, GPS, GSM, LoRa, WiFi and other UWB applications. The antenna offers average gain 2.59 dBi over entire operating frequency range and validates compatibility for spectrum sensing in WCRSN as per FCC standards.